Effects of intercropping rice and water spinach on net yields and pest control: an experiment in southern China. Issue 4 (1st October 2016) - Liang, Kaiming; Yang, Tao; Zhang, Shaobin; Zhang, Jia-en; Luo, Mingzhu; Fu, Ling; Zhao, Benliang
Abstract : Strategies encouraging the use of fewer agrochemicals while maintaining high yield are highly demanded for smallholder rice farmers. Intercropping helps to suppress pests and disease in upland farming systems. However, information on the role of intercropping in pest suppression and crop productivity in irrigated rice farming systems is sparse. To explore the possibility of establishing diversified agriculture management strategy that requires lower agrochemical inputs, a field study was conducted to evaluate the effect of rice and water spinach intercropping on the occurrence of pests, disease, and land-use efficiency. Results demonstrated that the occurrence of rice blast disease, sheath blight disease, and Cnaphalocrocis medinalis was substantially lower than pure stands. Compared with rice monoculture, the tiller number, net photosynthetic rate, and leaf chlorophyll content were significantly increased in rice at the edge rows adjacent to water spinach in intercropping. Intercropping increased the per unit area yield of rice without significant reduction in that of water spinach. Land equivalent ratio (LER) was 1.13, showing that intercropping was 13% more productive than rice monocropping. Net income for intercropping was 5.04 times higher than for rice monocropping. These findings suggest that rice and water spinach intercropping is a viable alternative for sustainable rice production with a small farming scale in southern China.